Exploring Four Decades of Research Trends in Islamic Banking: Directions, Themes, and Emerging Issues - Rachma Bhakti Utami; Rashid Ating; Afiqah Amin (Department of Islamic Economics, IPB University, 2026)
Islamic finance has grown significantly in recent decades, with Islamic banks and financial institutions operating not only in Muslim-majority countries but also in other regions. Conducting bibliometric studies to analyse trends in Islamic banking is crucial for addressing pressing global challenges, identifying knowledge gaps, guiding policy decisions, and fostering collaboration among scholars. This study aims to explore research patterns, collaboration networks, and thematic trends in publications on Islamic banking. Furthermore, this research seeks to see what further research can be conducted on Islamic banking. Examining 3115 papers published between 1983 and 2023 from the Scopus database using the Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) framework, this research utilizes R-Biblioshiny software for analysis. The study reveals a remarkable 66% increase in literature on Islamic banking. Notably, the International Islamic University Malaysia emerges as the most productive institution, while Malaysia, Indonesia, Pakistan, and the United Kingdom lead in productivity. Surprisingly, nations with non-Muslim-majority populations like the UK, USA, Australia, and the Netherlands garner the most citations. The extensive involvement of 88 countries in this literature underscores the global significance of Islamic banking, drawing interest from diverse authors worldwide. Moreover, the research categorizes four decades of Islamic banking studies into four thematic groups. This study reflects the transition of topics from traditional themes, such as riba, to the newest topics, such as corporate governance and financial technology. These findings offer valuable insights for understanding the evolving knowledge of Islamic banking research and identifying emerging research areas.